PENGEMBANGAN SIMULASI STRUCTURAL HEALTH MONITORING UNTUK DETEKSI DAN LOKALISASI CACAT PADA PELAT ISOTROPIK MENGGUNAKAN LAMB WAVE - Hamzah Farrasamulya, Muhammad
Structural Health Monitoring (SHM) is an inspection system characterized by a permanent distribution of sensors/transducers network on a structure to detect anomalies/defects in fast and autonomous manner. Application of SHM to aircraft structure can possibly decrease the structural margin of safety and also optimize the currently applied inspection and maintenance practices. Among many form of SHM methods, Lamb wave propagation phenomena on plate structure has been intensively researched. The focus of this final project is divided into two aspects. The first aspect is to develop finite element model to simulate Lamb wave actuation, propagation, and sensing for isotropic plate. Lamb wave actuation and sensing are conducted using PZT transducers modelled as piezoelectric element and analyzed using dynamic implicit procedure. Actuator input and sensor output are in the form of time- dependent voltage signal. Wave propagation is modelled twice each for healthy and damaged plate to get a pair of comparable signals using dynamic explicit analysis procedure. Explicit-Implicit Co-simulation procedure is utilized to combine the simulation of transducers and plate. Types of damage studied are through-thickness crack and two dimensional circular damage. The second aspect is to develop signal processing and damage location imaging program. Hilbert Transformation and Auto-correlation are the main methods employed in the time-domain-based signal processing program to extract Time of Flight (TOF) feature of the damage-scattered wave. Damage location imaging process is conducted by means of damage ellipses triangulation created by several TOFs obtained from different sensors in the network. A sequential finite element model development has been done using ABAQUS to get a final model that can show how Lamb wave can be generated and sensed by PZT transducers and can show how a damage can cause a damage-scattered wave. Furthermore, a signal processing and damage localization program has been developed using MATLAB to process the voltage signal acquired from sensors in the finite element model to get a visual imagery data representing the most probable damage location on the plate. Additional works included are parametric studies that investigate the influence of crack length and input excitation frequency variation to the signal characteristics obtained at the sensor.